Inovasi Pengembangan Minuman Mocktail Berbasis Bahan Rempah Lokal Untuk Peningkatan Pendapatan Masyarakat Kampung Adat Cireundeu - Nova Yudha Andriansyah Putra; Dyah Mustika Wardani; Mezi Julian (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Cireundeu comes from the name "reundeu tree", because previously in this village there was a large population of reundeu trees. The reundeu tree itself is a tree used for herbal medicine. Therefore, this village is called Cireundeu Village. Cireundeu Traditional Village is located in Leuwigajah Village, South Cimahi District. Consists of 50 heads of families or 800 people, most of whom make their living by farming cassava. Cireundeu Traditional Village itself has an area of ​​64 ha, consisting of 60 ha for agriculture and 4 ha for settlement. This service aims to explore the potential of local spice ingredients in creating mocktail drinks that are healthy and beneficial for local community income. Through collaboration between communities, universities and local industry, it is hoped that new innovations can be created that support the local economy while promoting healthy lifestyles. The output that will be produced in this PM is how the people of Cireundeu can utilize local plants to become classy ingredients that can compete with industry or as ingredients for mocktail drinks which can attract tourists to visit the village and become a multiplier effect for the local economy in the form of a press release publication. and Journals and IPR.